UMP receives face masks and jumpsuits from HBU China - UMP, PNC (2020)
After a month when Universiti Malaysia Pahang (UMP) contributed medical gloves for medical personnel at Hebei University China (HBU) during the Covid-19 outbreak, UMP received face masks and jumpsuits as one of personal protective equipment (PPE) from HBU for the frontliners on 7 April 2020.